Pengaruh Penerapan Pembelajaran Matematika Realistik (PMR) Berbantuan Whatsapp terhadap Hasil Belajar Matematika pada Siswa Kelas VII SMP Negeri 13 Mataram Tahun Pelajaran 2021/2022 - Aji Ramdana Siling; Nyoman Sridana; Nani Kurniati; Sripatmi Sripatmi (Griya Journal of Mathematics Education and Application, 2022)
This study aims to determine the effect of the WhatsApp-assisted realistic mathematics learning model (PMR) on the mathematics learning outcomes of seventh grade students of SMPN 13 Mataram in the 2021/2022 academic year. This type of research is a quasi-experimental study with Posttest Only Control Group Design which is a form of research method. Experiment. The population in this study were seventh grade students of SMPN 13 Mataram, the sample technique used was cluster random sampling. The samples of this study were students of class VII (I) as the experiment class and class VII (J) as the control class with a total of 33 students. The instruments used are lesson plans and student learning outcomes test sheets (posttest) on the set material. The data analysis used was the t test to see differences in learning outcomes, and the effect size test to see how much influence the realistic mathematics learning model (PMR) had on students' mathematics learning outcomes. Based on the results of the posttest data analysis using the t-test, it was found that t_count = 2.1457 > t_table = 1.1998 with a significant level of 5%, so H_0 was rejected and the effect size test was d = 0.5408 (medium). So it can be concluded that learning using the realistic mathematics learning model (PMR) assisted by WhatsApp has a significant effect on the mathematics learning outcomes of seventh grade students of SMPN 13 Mataram in the 2021/2022 academic year.